PENGARUH PENGGUNAAN KEY OPINION LEADER TASYA FARASYA TERHADAP MINAT BELI PRODUK KECANTIKAN GENERASI Z DI WILAYAH KOTA BANDUNG - Nadia Rizky Vindiazhari (Business Preneur: Jurnal Ilmu Administrasi Bisnis, 2024)
Key Opinion Leader (KOL), Tasya Farasya, is becoming an important strategy in influencing the purchasing decision of the beauty products industry for Generation Z in the Bandung City Area. Through the regression test method, it produced an R Square of 74.3%, which indicates that around 74.3% of the influence of KOL Tasya Farasya on buying interest of Generation Z beauty products in the Bandung City Area. Keywords: Key Opinion Leadr (KOL), Buying Interest, Generation Z